TEORI KOMPENSASI EMOSI - Mardeli Mardeli (Tadrib: Jurnal Pendidikan Agama Islam, 2016)
Growth and emotional development, as well as in other behaviors, is determined by a process of maturation and learning processes. A newborn baby has been able to cry, but he almost reached a certain level of maturity before he could laugh. If the child is older, he will learn that crying and laughing can be used for certain purposes in certain situations. In newborns, the only real emotion is anxiety that appear as displeasure in the new cry and struggled. In general, our daily actions accompanied by certain feelings, the feelings of pleasure or displeasure. Feelings of pleasure or displeasure that always accompanies / deeds of our daily called Effective Colors. Effective color is sometimes strong, sometimes weak or vague. The difference between feelings and emotions can not be stated emphatically, as both a qualitative continuity that is not undefined. At a certain moment, an effective color can be described as a feeling, but it can also be said as emotion. So, once we define difficult emotions. Therefore, what is meant by emotion here is not limited to emotions or feelings, but includes any circumstances in a person who is accompanied by a color effectively, both at the weak (shallow) as well as at the level of the (deep).